2011
DOI: 10.1158/0008-5472.can-10-2426
|View full text |Cite
|
Sign up to set email alerts
|

CARM1 Is an Important Determinant of ERα-Dependent Breast Cancer Cell Differentiation and Proliferation in Breast Cancer Cells

Abstract: Breast cancers with estrogen receptor a (ERa) expression are often more differentiated histologically than ERa-negative tumors, but the reasons for this difference are poorly understood. One possible explanation is that transcriptional cofactors associated with ERa determine the expression of genes which promote a more differentiated phenotype. In this study, we identify one such cofactor as coactivator-associated arginine methyltransferase 1 (CARM1), a unique coactivator of ERa that can simultaneously block c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 47 publications
3
82
2
Order By: Relevance
“…ERα is believed to regulate expression of genes involved in cell survival and proliferation, thus promoting tumor growth and differentiation, while the function of ERβ has been found to be anti-proliferative and pro-apoptotic. [20][21][22][23] ERβ has several splicing variants, including ERβ1 (wild type), ERβ2 (identical to ERβcx), ERβ3, ERβ4, ERβ5, and ERΔ5. 24,25 Interestingly, ERβ1 has been shown to act as a tumor suppressor, 26 and its expression declines during breast cancer progression.…”
Section: Lapatinib Induces P27mentioning
confidence: 99%
“…ERα is believed to regulate expression of genes involved in cell survival and proliferation, thus promoting tumor growth and differentiation, while the function of ERβ has been found to be anti-proliferative and pro-apoptotic. [20][21][22][23] ERβ has several splicing variants, including ERβ1 (wild type), ERβ2 (identical to ERβcx), ERβ3, ERβ4, ERβ5, and ERΔ5. 24,25 Interestingly, ERβ1 has been shown to act as a tumor suppressor, 26 and its expression declines during breast cancer progression.…”
Section: Lapatinib Induces P27mentioning
confidence: 99%
“…We had previously identified CARM1-regulated ERα target genes using microarrays (4). To establish the functional role of PAF1c in CARM1-regulated transcription, we attempted to knockdown PAF1c components and measure the effects on mRNA levels of CARM1-regulated ER targets.…”
Section: Paf1c and Carm1 Coordinately Regulate A Common Set Of Erαmentioning
confidence: 99%
“…Loss of CARM1 in the mouse embryo leads to abrogation of the estrogen response and reduced expression of some estrogen receptor-α (ERα) target genes (3). Recently, CARM1 was shown to be a unique coactivator of ERα that can simultaneously block cell proliferation and induce differentiation through global regulation of ERα-regulated genes in breast cancer cells (4). The methyltransferase activity of CARM1 is required for its ability to regulate transcription of pS2 (TFF1), a standard ERα target gene (5).…”
mentioning
confidence: 99%
“…Estrogen-stimulated ERα recruits coactivators, which often carry histone modification activities, to coordinate with basal transcription machineries to achieve productive cycles of transcription (Kininis et al 2009). Coactivator-associated arginine methyltransferase 1 (CARM1) is a potent coactivator of ERα, which specifically deposits the active histone mark H3R17me2a (Chen et al 1999;Al-Dhaheri et al 2011) near the promoter of target genes. We previously showed that the human RNA polymerase II (RNAPII)-associated factor complex (hPAFc) interacts directly with H3R17me2a and that this association is required for productive transcriptional initiation and elongation of the pS2 gene in MCF7 breast cancer cells (Wu and Xu 2012).…”
mentioning
confidence: 99%